Beverage Consumption and Longitudinal Changes in Lipoprotein Concentrations and Incident Dyslipidemia in US Adults: The Framingham Heart Study - Haslam, Danielle E.; Peloso, Gina M.; Herman, Mark A.; Dupuis, Josée; Lichtenstein, Alice H.; Smith, Caren E.; McKeown, Nicola M. (Journal of the American Heart Association, 2020)
Background Limited data are available on the prospective relationship between beverage consumption and plasma lipid and lipoprotein concentrations. Two major sources of sugar in the US diet are sugar-sweetened beverages (SSBs) and 100% fruit juices. Low-calorie sweetened beverages are common replacements. Methods and Results Fasting plasma lipoprotein concentrations were measured in the FOS (Framingham Offspring Study) (1991-2014; N=3146) and Generation Three (2002-2001; N=3584) cohorts. Beverage intakes were estimated from food frequency questionnaires and grouped into 5 intake categories. Mixed-effect linear regression models were used to examine 4-year changes in lipoprotein measures, and Cox proportional hazard models were used to estimate hazard ratios for incident dyslipidemia, adjusting for potential confounding factors. We found that regular (>1 serving per day) versus low (<1 serving per month) SSB consumption was associated with a greater mean decrease in high-density lipoprotein cholesterol (β±standard error -1.6±0.4 mg/dL; <0.0001) and increase in triglyceride (β±standard error: 4.4±2.2 mg/dL; =0.003) concentrations. Long-term regular SSB consumers also had a higher incidence of high triglyceride (hazard ratio, 1.52; 95% CI, 1.03-2.25) compared with low consumers. Although recent regular low-calorie sweetened beverage consumers had a higher incidence of high non-high-density lipoprotein cholesterol (hazard ratio, 1.40; 95% CI, 1.17-1.69) and low-density lipoprotein cholesterol (hazard ratio, 1.27; 95% CI, 1.05-1.53) concentrations compared with low consumers, cumulative average intakes of low-calorie sweetened beverages were not associated with changes in non-high-density lipoprotein cholesterol, low-density lipoprotein cholesterol concentrations, or incident dyslipidemias. Conclusions SSB intake was associated with adverse changes in high-density lipoprotein cholesterol and triglyceride concentrations, along with a higher risk of incident dyslipidemia, suggesting that increased SSB consumption may contribute to the development of dyslipidemia.